2018
DOI: 10.3892/mmr.2018.8678
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29c inhibits proliferation and promotes apoptosis in non-small cell lung cancer cells by targeting VEGFA

Abstract: Non-small cell lung cancer (NSCLC) is a primary sub-type of lung cancer with a high incidence rate and poor prognosis. The primary therapeutic treatment for NSCLC is chemotherapy, which is considered to be ineffective and excessively toxic. Novel therapeutic methods, particularly molecular targeted therapy, have attracted considerable attention. MicroRNAs (miRs) are reported to be potential biomarkers and targeted agents with roles in various types of tumors. Herein, the present study presented the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…In the present study, five differentially expressed miRNAs were all upregulated in metastatic melanoma tissues, including miRNA-29c, miRNA-100, miR-142-3p, miR-150, miR-516a-2, and the upregulation of each differential miRNA was positively correlated with patient survival time, indicating that these five miRNAs might be inhibitory factors of melanoma metastasis. In previous studies, miRNA-29c has been shown to be downregulated in prostate cancer and non-small cell lung cancer (NSCLC) [22,23]. Also, miRNA-100 [24], miR-142-3p [25] and miR-150 [26] have previously been reported to inhibit the proliferation of gastric cancer cells, liver cell cancer cells and melanoma cells in vitro , through the targeted suppression of the CXCR7, LDHA, and MYB genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, five differentially expressed miRNAs were all upregulated in metastatic melanoma tissues, including miRNA-29c, miRNA-100, miR-142-3p, miR-150, miR-516a-2, and the upregulation of each differential miRNA was positively correlated with patient survival time, indicating that these five miRNAs might be inhibitory factors of melanoma metastasis. In previous studies, miRNA-29c has been shown to be downregulated in prostate cancer and non-small cell lung cancer (NSCLC) [22,23]. Also, miRNA-100 [24], miR-142-3p [25] and miR-150 [26] have previously been reported to inhibit the proliferation of gastric cancer cells, liver cell cancer cells and melanoma cells in vitro , through the targeted suppression of the CXCR7, LDHA, and MYB genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…S9). However, miR-29c and miR-30b were shown as tumor suppressor miRNAs in lung cancer [17,[28][29][30][31][32][33]. Oncogenes such as myc, gli, and NF-κb can bind to the promotor region of miR-29c to suppress its transcription in cholangiocarcinoma cells [34].…”
Section: Discussionmentioning
confidence: 99%
“… 16 The 5-year survival rate of lung cancer is poor due to the high invasion and metastasis of tumors. 3 In recent years, multiple miRNAs have been reported to play a functional role in the occurrence and progression of lung cancer. 5 The present study explored the effects of miR-210-3p on cell viability, migration, invasion, and apoptosis in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 2 For instance, miR-29c regulates cell proliferation and cellular apoptosis that in turn affects the tumor progression of NSCLC. 3 Existing literature reported that miR-18a-5p is upregulated in NSCLC, and it promotes cell proliferation and migration, tumor growth, and metastasis of NSCLC both in vitro and in vivo to aggravate lung cancer. 17 miR-210 is also shown to play a significant role in a variety of tumor biological functions, including tumor proliferation, survival, and metastasis via regulation of target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation